Kompleksnyj analiz metabolitov energoobespecenija i ergometriceskich dannych pri standartnom testirovanii plovcov vysokoj kvalifikacii - Shirkovets, E. A.; Rybina, I. L. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The article presents a comparison of the dynamics of the complex of biochemical parameters, often used in sports practice, when performing a standard test with a step-increasing load performed to failure. The study compares the diagnostic specificityof ergometric, metabolic, enzymatic and hematological parameters. The analysis of the considered data makes it possible to assess the reliability of laboratory tests used to identify the information content of biochemical criteria for the functioning of the body systems of athletes in the process of intense muscle work.